Relocation to an activity-based flexible office – Design processes and outcomes. (November 2018) - Rolfö, Linda Victoria
Abstract: Many organizations relocate to activity-based flexible offices (A-FOs) and the results are mixed. This study aims at identifying factors in the design and implementation process that contribute to perceived performance and environmental satisfaction with A-FOs. A company with 50 employees was studied using interviews, questionnaires and documentation before and after relocation. The results showed that process factors such as objectives, financial and time resources, employee participation and empowerment, and methodological approach contributed to the outcomes. Perceived performance and employee satisfaction with the physical environment increased significantly after the relocation. Employee empowerment, highlighted by the employees, correlated with the performance and satisfaction parameters. A conceptual model is proposed relating process factors, internal and external organizational context, and physical office setting to work condition consequences and overall outcomes such as employee performance and satisfaction. Graphical abstract: Image 1 Highlights: Objectives, financial and time resources, and methodology are central process factors. Employee empowerment correlates with performance and environmental satisfaction. Performance and satisfaction can increase significantly after relocation to an A-FO. A conceptual model is proposed for supporting the design processes of offices.